Judgment or Hope? Quantifying Frequent and Abrupt Changes in the Emotion of Language from the Book of Isaiah - Whissell, Cynthia (Advances in Social Sciences Research Journal, 2021)
A quantification of the pleasantness of text from the Biblical book of Isaiah (NIV translation) using the Dictionary of Affect in Language indicates that the work has many abrupt changes in emotional tone (p<.05) between its 102 segments. Changes are in line with commentators’ description of the book as a mixture of hope and judgment. Confusion experienced by inexperienced readers of this work could be the result of the recurrent and often un-signaled changes in emotional tone.